Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/15384101.2017.1282583
|View full text |Cite
|
Sign up to set email alerts
|

Smc1β is required for activation of SAC during mouse oocyte meiosis

Abstract: Smc1β is a meiosis-specific cohesin subunit that is essential for sister chromatid cohesion and DNA recombination. Previous studies have shown that Smc1β-deficient mice in both sexes are sterile. Ablation of Smc1β during male meiosis leads to the blockage of spermatogenesis in pachytene stage, and ablation of Smc1β during female meiosis generates a highly error-prone oocyte although it could develop to metaphase II stage. However, the underlying mechanisms regarding how Smc1β maintains the correct meiotic prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…With extended aging time, oocytes displayed a remarkably increasing proportion of poorly expanded cumulus cells and fragmented cytoplasm, which suggests that apoptosis occurs in postovulatory aged oocytes. Previous studies have shown that aging would lead to defective spindle assembly and chromosome alignment in mouse oocytes, which subsequently induces the production of aneuploid eggs (23)(24)(25)(26)(27). Our observations in porcine oocytes were consistent with these reports in that they demonstrated the spindle and chromosome abnormalities after postovulatory aging in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…With extended aging time, oocytes displayed a remarkably increasing proportion of poorly expanded cumulus cells and fragmented cytoplasm, which suggests that apoptosis occurs in postovulatory aged oocytes. Previous studies have shown that aging would lead to defective spindle assembly and chromosome alignment in mouse oocytes, which subsequently induces the production of aneuploid eggs (23)(24)(25)(26)(27). Our observations in porcine oocytes were consistent with these reports in that they demonstrated the spindle and chromosome abnormalities after postovulatory aging in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…Manuscript to be reviewed activates the APC/C activity to accelerate SECURIN degradation and anaphase I onset (Marston et al, 2017 ). Defects in SAC function can result in incorrect attachments of chromosome with microtubules, and leads to missegregation (Miao et al, 2017;Lu et al, 2017;Li et al, 2009). Study has shown that knockdown of BRCA1 causes abnormal spindles in mouse oocytes (Xiong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by us and others have indicated that oocyte meiotic arrest is largely caused by the activation of spindle assembly checkpoint induced by the defective spindle assembly and chromosome alignment. 2,3,5,28 Meanwhile, it has been reported that dynein is required for the association of chromosomes with astral microtubules during in vitro meiosis I spindle assembly in the cytoplasmic extracts of Spisula solidissima oocytes. 32 Dynein light intermediate chain 1 participates in the spindle assembly checkpoint silencing via removal of Mad1/2 and Zw10 but not BubR1 from kinetochores in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate control of spindle assembly and chromosome separation is obligatory for orderly meiosis during oocyte maturation, where any errors in this process can lead to the generation of aneuploid eggs. [2][3][4][5] Microtubule polymerization is regulated by a number of microtubule-associated proteins including motor proteins such as cytoplasmic dynein and kinesins 6,7 which can directly interact with microtubule ends to modulate the microtubule length and dynamics. 7,8 Dynein, a large protein complex, drives long-range retrograde transport along microtubules and carries a wide range of cargos to play a vital role in cellular processes as diverse as spindle positioning, chromosome movement, Golgi dynamics and centrosome assembly etc.…”
Section: Introductionmentioning
confidence: 99%